ANALISA KUALITAS HIDUP PASIEN DENGAN CA MAMMAE DI MURNI TEGUH MEMORIAL HOSPITAL - Ivlan Andiani Waruwu; Seriga Banjarnahor (PT. Hasba Edukasi Mandiri, 2025)
Background : Cancer is one of the main causes of death in the world. The incidence of breast cancer ranks second in the world. Breast cancer is an abnormal cell growth in the breast which can sometimes be felt as a lump or mass which is often called a tumor. Quality of life is a person's ability to carry out daily physical, psychological and social activities. Quality of life can be considered good if a person can control his illness and all the organs in his body still function well. Quality of life is used in the field of health services to analyze a person's emotional, social factors, and ability to meet the demands of normal life activities and the impact of illness which has the potential to reduce health-related quality of life. Objective : To analyze the quality of life of ca mammae patients. Method : This research uses a descriptive method. Sampling used Total Sampling with a total sample of 42 respondents. The research instrument used was a questionnaire assessment from WHOQOL-BREF. Results : Results of data analysis using the Spearman Rho test. Conclusion : The majority of quality of life for ca mammae patients at Murni Teguh Memorial Hospital is in the Good Category. There is a relationship between education and the quality of life of ca mammae patients with a p-value of 0.043.